Redescription of Austrothelphusa wasselli (Bishop, 1963) (Crustacea: Brachyura: Gecarcinucidae), and designation of a new species from the Gilbert River, north Queensland, Australia - Naser, Murtada D.; Davie, Peter J. F.; Waltham, Nathan J. (Zootaxa, 2018)
A new species of freshwater crab, Austrothelphusa gilbertensis, is described from Gilbert River Catchment, north-western Queensland. It is morphologically most similar to A. wasselli Bishop, 1963, described from the eastward flowing Stewart Drainage Basin, much further to the north-east on Cape York. It differs from A. wasselli by several morphological characters including, better defined gastro-cardiac carapace grooves, cervical groove relatively deeper, postfrontal lobes more prominent and bearing striated crests, larger and fewer spots on carapace and legs, epibranchial tooth more prominent, walking legs more slender, and G1 more strongly curved. A CO1 genetic divergence of greater than 6% confirms its novel status. Intraspecific CO1 divergence within catchments is also discussed.